STUDI KUANTITATIF KONTRIBUSI KONTEN PROMOSI INSTAGRAM @jumbofilm_id TERHADAP PEMBENTUKAN KEPUTUSAN MENONTON PADA FOLLOWERS - Marsya Regitha Avantie; Hudi Santoso; Enden Darjatul Ulya; Fahmi Fuad Cholagi (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study examines the influence of Instagram promotional content by @filmjumbo_id on its followers' viewing decisions. The purpose of this study is to determine how aspects of information delivery, interaction, and personalization in promotional content influence audience behavior. The method used is a descriptive quantitative with an explanatory survey approach involving 100 respondents who are active followers of the @filmjumbo_id account. Data analysis includes testing validity, reliability, correlation, and simple linear regression. All research instruments were proven valid (r-count > 0.361) and reliable (Cronbach's Alpha for promotional content = 0.812; for viewing decisions = 0.747). The results of the correlation analysis showed a strong and significant positive relationship (r = 0.854, p < 0.001). The simple regression equation Ŷ = -1.864 + 1.168X indicates that promotional content has a positive and significant influence on viewing decisions, with an R² value of 0.729, meaning 72.9% of the variation in viewing decisions is explained by promotional content. The results of this study also enrich our understanding of the role of social media promotional content in the context of digital marketing communications. Furthermore, these findings can serve as a reference for film promotion managers in designing more effective Instagram content strategies to drive audience viewing decisions. Keywords: Digital Marketing Communication, Film Promotion, Instagram, Promotional Content, Viewing Decisions